Research on Foreign Air-to-Air Missiles’Development in 2024 - Ren Miao, Liu Jingjing, Wen Lin (Hangkong bingqi)
This paper gives a full description of development of foreign air-to-air missiles in 2024. It presents the latest advancement of AIM-9X, AIM-120,AIM-260, AIM-174B, LongShot program, Modular Advanced Missile, air dominance technologies, ASRAAM, Meteor,IRIS-T, FCAAM, FSRM, and Article 810, Astra BVRAAM, SKY STING, Stunner Missile, etc. In the end, the paper summarizes the new development features of air-to-air missiles.